Positive correlation between the nuclear expression of GPER and pGLI3 in prostate cancer tissues from patients with different Gleason scores - Rico-Fuentes, Cecilia; López-Pulido, Edgar Iván; Pérez-Guerrero, Edsaúl Emilio; Godínez-Rubí, Marisol; Villegas-Pineda, Julio César; Villanueva-Pérez, Martha Arisbeth; Sierra-Díaz, Erick; Zepeda-Nuño, José Sergio; Pereira-Suárez, Ana Laura; Ramírez-de-Arellano, Adrián (Frontiers in Endocrinology, 2024)
Prostate cancer (PCa) is the most prevalent cause of death in the male population worldwide. The G Protein-Coupled Estrogen Receptor (GPER) has been gaining relevance in the development of PCa; however, the regulation it exerts over signaling pathways is not fully understood yet. Hedgehog (Hh) pathway activation is associated with aggressiveness, metastasis, and relapse in PCa patients. To date, no studies have evaluated the crosstalk between the GPER and the Hh pathway along different group grades in PCa. Therefore, in this study, we evaluated the expression and correlation between GPER and glioma-associated oncogene homologue (GLI) transcriptional factors in the parenchyma and stroma of tumors belonging to PCa patients with different group grades. Our results indicate that GPER is highly expressed in the nucleus, and it increases as the group grades are higher. Besides, the GPER´s expression correlates with pGLI3 nuclear expression along the different group grades. There is a correlation between the GPER´s expression and GLI transcriptional factors in PCa tissues; however, whether the receptor induces the activation of GLI transcriptional factors or the latter modulate the expression of GPER is yet to be discovered, as well as the functional consequence of this correlation.